SUMBANGAN PENGAJIAN KURSUS TAMADUN ISLAM DAN TAMADUN ASIA (TITAS) TERHADAP PEMBENTUKAN HATI BUDI MAHASISWA DI INSTITUSI PENGAJIAN TINGGI AWAM (IPTA) MALAYSIA (Contribution of the Islamic and Asia Civilization (TITAS) towards Holistic Formation of Students - Che Husain, Faridah; Abdul Kadir, Fakhrul Adabi (Journal of Al-Tamaddun, 2012)
Course of Islamic and Asian Civilization (TITAS) is known as one of the compulsory courses in each universities in Malaysia. Direction from the Ministry of Education Malaysia has made TITAS as compulsory course at Higher Learning Institutions (IPT). This was appropriate step towards achieving the concept of universities as providers of knowledge to develop a holistic student. Implementation of TITAS as compulsory course is in line with national aspirations which are sensitive to changes of the current curriculum needed to produce the country?s, market?s and student?s needs. It was drafted by representatives from local universities, the course is offered to all undergraduate students starting from the academic session 1998/1999. TITAS courses are based on the unique content which are required for all students of the Institute of Higher Learning (IPT), regardless of their field of study. The formation is in such a way that it embeddes oneself indirectly in the course of study to educate student?s morality. Strengthening the perfect human can produce students who are the human welfare of a community and being an agent of continuous expansion of civilization. Therefore, this article will focus on the literature review including the concept of oneself, the morality, factors that forming students? oneself, and contribution of TITAS to the formation of good students.